Analisa Optimasi Biaya Dan Waktu Metode TCTO (Time Cost Trade Off) (Study Kasus: Preservasi Jalan Ruas Sp. Gunung Kemala – Sanggi) - Aziz Irawan, Yusuf; Suharto; Juara, Agus (Jurnal Civil Engineering Study, 2022)
The success of a project can be measured from two things, namely the benefits obtained and the timeliness of completion. In the implementation of the Gunung Kemala-Sanggi road preservation project, there are indications of delays where in contract 01 there is a remaining unfinished work resulting in contract 02, so it needs to be accelerated. This is intended so that this project can be completed more quickly according to the planned target. The acceleration method used is Time Cost Trade Off, with the alternative of adding 1 hour of overtime. This research methodology has several stages including primary data collection such as road preservation data and location data, as well as secondary data such as literature review, budget plan data (rab), project time schedule data, monthly report data. From the alternative results of adding overtime hours to the Kemala-Sanggi Mountain Road preservation project, it was found that the acceleration duration was 89 days from the previous duration of 112 days, 23 days faster so that the implementation of the work can be in accordance with the initial scheduling plan obtained from the project S curve. The reduction in the final total cost of the project due to acceleration is Rp. 687,273,911 so that the total cost of the project becomes Rp. 21,567.130,687. from the previous total value of Rp 22,186,544,124. It is hoped that further research can develop research on time cost trade off analysis, for example by developing an analysis by calculating labor overtime wages, operating costs of equipment when used for overtime or adding the number of tools.